Peran DPRK Aceh Utara dalam Menjalankan Fungsi Anggaran - Nurhaslita Sari; Arfriani Maifizar; Sri Wahyu Handayani; Agus Pratama; Nurasma Aripin; Fitria Mustika (Jurnal Public Policy, 2021)
This study discusses the shape and obstacles of policy control of North Aceh's Revenue and Expenditure Budget in 2020. This study aims to find out how the form and obstacles of monitoring the policy of Revenue and Expenditure Budget of North Aceh Regency in 2020. The method used in this paper is a descriptive qualitative research method. The authors collected data from multiple sources of research books, encyclopedias, journals and interviews with informants of the study. The results showed the form of monitoring of budget policy of North Aceh District Expenditure has not been carried out effectively, because only political. there are obstacles, such as education background of North Aceh DPRK member, political factor and lack of databases in monitoring the APBK North Aceh policy in 2020.